2008
DOI: 10.1002/met.71
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study among different neural net learning algorithms applied to rainfall time series

Abstract: ABSTRACT:The present article reports studies to identify a non-linear methodology to forecast the time series of average summer-monsoon rainfall over India. Three advanced backpropagation neural network learning rules namely, momentum learning, conjugate gradient descent (CGD) learning, and Levenberg-Marquardt (LM) learning, and a statistical methodology in the form of asymptotic regression are implemented for this purpose. Monsoon rainfall data pertaining to the years from 1871 to 1999 are explored. After a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 35 publications
0
25
0
Order By: Relevance
“…Selvam et al, 1995;Sivakumar, 2001;Dix and Hunt, 2007;Chattopadhyay and Chattopadhyay, 2008a) and the suitability of an ANN in dealing with chaotic time series is well established (Prinicipe et al, 1992). In the present study, the ANN approach has been adopted to forecast precipitation in a time step ahead.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Selvam et al, 1995;Sivakumar, 2001;Dix and Hunt, 2007;Chattopadhyay and Chattopadhyay, 2008a) and the suitability of an ANN in dealing with chaotic time series is well established (Prinicipe et al, 1992). In the present study, the ANN approach has been adopted to forecast precipitation in a time step ahead.…”
Section: Introductionmentioning
confidence: 98%
“…Hung et al (2008) used meteorological parameters in developing an ANN rainfall forecast models. Chattopadhyay (2007) applied an ANN in the form of multilayer perceptron to forecast monsoon rainfall over India using some meteorological predictors and Chattopadhyay and Chattopadhyay (2008a) compared the performances of various backpropagation learning algorithms in forecasting monsoon rainfall time series using the monthly mean rainfall amounts as predictors. Chattopadhyay and Chattopadhyay (2008b) compared the performances of different ANNs with variable hidden layer size in forecasting rainfall time series.…”
Section: Introductionmentioning
confidence: 99%
“…It should be mentioned that there is no strict rule to decide the ratio of training and test cases. A survey of the ANN literature found that the ratios 1 : 1 (Chattopadhyay and Chattopadhyay, 2008a), 7 : 3 (Lundin et al, 1999) and 3 : 1 (Perez et al, 2000) are frequently used in ANN applications. In the present paper an approach similar to that of Lundin et al (1999) has been adopted after examining the other approaches.…”
Section: Development Of Artificial Neural Network Modelmentioning
confidence: 99%
“…Willmott's indices of order 1 and 2, which are highly acceptable measures of goodness of fit (Willmott, 1982;Chattopadhyay and Chattopadhyay, 2008a) in meteorological modelling, are given in Table III. It is revealed that the maximum values of Willmott's indices of order 1 and 2 are produced in June and the values 0.657 (for order 1) and 0.873 (for order 2) are considerably high in this case.…”
Section: The Measure Of Error Of Estimation (Ee) Is Expressedmentioning
confidence: 99%
“…Their model results 0.8 correlations between actual and predicted rainfall. Surajit and Goutami Chattopadhyay (2008) identify a non linear methodology to forecast the time series of average summer monsoon rainfall over India [8]. The RMSE for four NN based techniques is 0.15, 0.26, 0.42 and 0.47.…”
Section: Introductionmentioning
confidence: 99%